Past and Present, Subalternity and Revolution - Fifi, Gianmarco (International Gramsci Journal, 2023)
This is a review by Gianmarco Fifi of the volume Revisiting Gramsci’s Notebooks (Leiden: Brill, 2020) that includes the proceedings of an international conference (“Past and Present”) held in London in 2017. The volume was edited by edited by Francesca Antonini, Aaron Bernstein, Lorenzo Fusaro and Robert Jackson.